Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8116387 ZenodoArchiveConcept: 8116386 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8116387 10.53832/edtechhub.0172 2339240:V4SEB3GI 2405685:V8CZHW5B 2405685:ZY6RMGAF
Keywords: _r:AddedByZotZen

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7074857 ZenodoArchiveConcept: 7074856 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6326179 10.5281/zenodo.7074857 10.53832/edtechhub.0114 2405685:K5BJUBRE 2405685:REW8F5TJ 2405685:U6G7C62D
Keywords: _r:AddedByZotZen

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10610797 ZenodoArchiveConcept: 10610796 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1007 2339240:SZE9FBW4 2405685:IIAMD77T
Keywords: _r:AddedByMyEducationEvidence

From the Helpdesk: Observations and guidance on educational response planning during the COVID-19 crisis (EdTech Hub, 2020)
Written by Rachel Chuang, Tom Kaye, Caitlin Moss Coflan & Arjun Upadhyay (EdTech Hub Helpdesk Management Team) Amid one of the biggest global disruptions to schooling in living memory, countries are quickly developing distance education responses for students. The EdTech Hub’s Helpdesk is providing evidence-informed responses to requests for support from governments and their partners as they face this challenge. …
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707838 2405685:84ZQF884
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11197419 ZenodoArchiveConcept: 11197418 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1027 10.53832/edtechhub.1028 2405685:DQ9GNC3J 2405685:M6A4ZHJ3
Keywords: _r:AddedByMyEducationEvidence

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

EdTech in Senegal: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
ZenodoArchiveID: 5652140 previousZenodoArchiveID: 3936687 previousshortDOI: 10/ghgnd2 previousDOI: 10.5281/zenodo.3936687 shortDOI: 10/ghgnd2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3936687 10.53832/edtechhub.0037 10/ghgnd2 2339240:EHTSKIBR 2339240:YQHNWNMB 2405685:5P5HVP47 2405685:BBP57X2K 2405685:SKFMQF3F 2405685:XI5PXVB3
Keywords: C:Senegal; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; pu

EdTech in Liberia: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
ZenodoArchiveID: 5652130 previousZenodoArchiveID: 3830953 previousshortDOI: 10/ghgk68 previousDOI: 10.5281/zenodo.3830953 shortDOI: 10/ghgk68 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3830953 10.53832/edtechhub.0033 10/ghgk68 2339240:XCBTX2XL 2405685:2HM2SBVM 2405685:FU7Z8QM7
Keywords: C:Liberia; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

Using Blended Learning to Support Marginalised Adolescent Girls’ Education: A Review of the Evidence - Allier-Gagneur, Zoé; Chuang, Rachel; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
This topic brief reviews evidence about the use of blended learning to support the education of marginalised adolescent girls in low- and middle- income countries.
ZenodoArchiveID: 4762319 previousDOI: 10.5281/zenodo.4762319 previousDOI: 10.5281/zenodo.4762319 previousDOI: 10.5281/zenodo.3952069 10.5281/zenodo.3952069 2405685:7PYD5JNV 2405685:H3AI5F3C 2339240:ENEKVCE3 2129771:FX6TFDPQ 2129771:9Q4PMCJN 2486141:TE93MW3V KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3952069 10.5281/zenodo.4762319 10.53832/edtechhub.0009 2339240:MU9RJZS3 2339240:WG969BFI 2405685:7PYD5JNV 2405685:A7IA7VZZ 2405685:H3AI5F3C 2405685:XMDKD3TS
Keywords: F: Helpdesk response; H:Blended learning; L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; dode_eth-src-eth; dode_eth-trf2-dode

Bandarban Sandbox: Needs assessment and hypothesis development - Tanweer, Rabia; Nashtaran, Trishia; Plaut, Daniel; Rahman, Asad; Ahmed, Shakil; Chowdhury, Dilruba; Rabbi, BM Fazley; Hoque, Rashedul; Nahar, Nurun; Afroze, Sadia (EdTech Hub, 2022)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners, working closely with the government and EdTech Hub to identify how EdTech can best be harnessed to support learning in Bangladesh. This partnership uses the sandbox approach — which provides a space for partners to test and grow ideas in conditions of uncertainty — to test how EdTech modalities that aim to improve numeracy outcomes for Grade 6 learners (early secondary) in Bandarban, one of the most remote areas of Bangladesh, can be used most effectively by learners and educators. This report outlines the process and findings from the needs assessment and hypothesis development phase. These findings (as well as the data collection which informs them) are organised around five research questions developed by EdTech Hub in partnership with Agami Education Foundation, the implementing agency for the sandbox. The findings of the research were distributed in themes that outlined the availability and utilisation of technology and a valid level of knowledge and interest in teachers and students towards using technology for education. While some findings shed light on the technical aspects of the context, some human factors also played a role in resisting the acceptance of technology in education. Building on the learning from this needs assessment phase, Agami Education Foundation and EdTech Hub have agreed to test this implementation plan in the upcoming staggered deployment phase. Keywords: EdTech; sandbox; numeracy; Bandarban; Bangladesh; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6942540 10.53832/edtechhub.0103 2339240:Y9SQVEU9 2405685:77665EVG 2405685:JV4F45P5
Keywords: _r:AddedByZotZen

Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
ZenodoArchiveID: 3744581 previousshortDOI: 10/ghgng7 previousDOI: 10.5281/zenodo.3744581 EdTechHub.Source: 2405685:2WY8H4WW EdTechHub.Source: <this> shortDOI: 10/ghgng7 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3744581 10.5281/zenodo.3744581 10.53832/edtechhub.0021 10/ghgng7 2129771:QEIBUIQH 2339240:3NRFPYGI 2339240:TK94XQR9 2339240:XJRI6FW3 2339240:Y635S3D4 2339240:Z7XXM8CG 2339240:ZZ8ISXSK 2405685:2WY8H4WW 2405685:6FFSC2Z8 2405685:DI4SGTPH 2405685:FLHI5BHC 2405685:FVE6PDBB 2405685:GG9HHSDL 2405685:PXAIRTEK 2405685:RLBPSG29
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
ZenodoArchiveID: 7267302 ZenodoArchiveConcept: 7267301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7267302 10.53832/edtechhub.0127 2339240:V7ARHU93 2405685:GBBGHCBH 2405685:QADQUWU3 2405685:UTTZNZ24
Keywords: _r:AddedByZotZen